PENGARUH SLOW DEEP BREATHING TERHADAP PENURUNAN TINGKAT KECEMASAN PASIEN PRE OPERASI SECTIO CAESAREA ( Effect Of Slow Deep Breathing To Decrease Rate Leather Patients Pre Operations Sectio Caesarea ) - Zahroh, Roihatul; Maslahatul, Dewi (Fakultas Keperawatan, Universitas Katolik Widya Mandala Surabaya, 2017)
Introduction: Anxiety is an unpleasant and unjustified fear that is often accompanied by physiological symptoms. Slow deep breathing is a conscious action to regulate deep and slow breathing that can have a relaxing effect. Doing slow deep breathing is one type of nonfarmakologis therapy that serves to relax and decrease the level of anxiety. The purpose of this study was to analyze the effect of slow deep breathing on decreasing the anxiety level of patients with preoperative sectiocaesarea.Slow deep breathing techniques done with draw breath slowly, in maximum, next hold the breath for 3 seconds then exhaled slowly (over 10 x permenit). Methods: This research uses One Group Pre test-Post test design. Samples taken as many as 46 respondents by using Purposive Sampling. The independent variables are slow deep breathing and the dependent variable decreases the anxiety level of the patients with preoperative sectiocaesarea. Results: This research data is taken by using observation and interview.The result of Wilcoxon signed rank test statistic in getting the result of decrease of anxiety level (ρ = 0,000) means that there is influence of slow deep breathing to decrease of anxiety level of patient pre operation sectiocaesarea. Discussion: Provision of slow deep breathing is needed for decreased anxiety. Slow deep breathing in addition to decreasing anxiety can also cause immediate psychological effects that can help give a relaxed feeling, relieve tension and relax.